Local Action Groups as a New Marketing Entity in Local Governments. A Case Study From the Lubelskie Province - Guzal-Dec, Danuta (Olsztyn Economic Journal, 2018)
This paper defines the scope and tools used within the framework of a marketing function, particularly including communications by Local Action Groups (LAGs). The aim of the research was to determine the significance of LAGs in the creation of a territorial product and the range of Public Relation (PR) applications by LAGs in the marketing communication of municipalities. This was achieved by means of a literature review, desk research and the analysis of documents including those that directly regulate the functioning of all 22 LAGs from the Lubelskie Province during the 2014 to 2020 period. According to the research results, the marketing activities of LAGs constitute a combination of activity with respect to product development and PR, activity related to the creation/development of tourism products and their promotion. The marketing activity of LAGs is a synergistic reinforcement of the marketing activity conducted by individual local governments in the area of product development and shaping of the image. LAGs are an entity actively participating in PR. They also enhance the catalogue of PR tools used by the administration of rural municipalities.